Nanocomposites based on poly(lactic acid) and bacterial cellulose acetylated by an α-hydroxyacid catalyzed route - Ávila Ramírez, Jhon Alejandro (2019)
Poly(lactic acid) (PLA) nanocomposite films reinforced with acetylated bacterial cellulose nanoribbons were prepared by solvent casting. Acetylation of bacterial cellulose (BC) was performed by an innovative and sustainable direct solvent-free route catalyzed by citric acid. The effect of derivatization and its extent on the morphological, optical, thermal and mechanical properties of the nanocomposites was analyzed. Data collected from the above studies showed that acetylation of BC nanoribbons clearly improved the nanofibers dispersion in the PLA matrix with respect to unmodified BC, which in turn resulted in increased transparency and mechanical properties of the nanocomposites produced.